TikTok-Integrated Project-based learning for EFL Speaking Development: A Qualitative Case Study in a Tertiary Context - Lisa Rakhmanina; Arono Arono; Wisma Yunita; Melati Melati; Kosiah Jalbani (AL-ISHLAH: Jurnal Pendidikan, 2026)
While TikTok has been increasingly explored in education, its role as a central pedagogical artefact in Project-Based Learning (PjBL) for tertiary EFL speaking development remains underexamined. This study investigates how TikTok storytelling projects and reflective writing facilitate students’ speaking skills.A qualitative case study was conducted with 14 tertiary EFL students in Indonesia. Data were collected through classroom observations, student-produced TikTok videos, reflective writings, and instructional documents. Analysis employed Brown’s speaking descriptors to identify patterns in students’ speaking performance and development.The integration of TikTok as a project artefact promoted iterative speaking practice, peer rehearsal, and continuous reflection. Rather than uniform improvement, students exhibited varied speaking development, including enhanced inquiry, collaboration, and reduced speaking anxiety. The reflective phase was particularly significant, enabling students to recognize their communicative abilities and address psychological barriers to speaking.The findings highlight the pedagogical value of combining social media platforms with PjBL to create authentic, engaging, and low-anxiety learning environments. Reflection played a crucial role in consolidating learning and fostering self-awareness in language use.TikTok-mediated PjBL offers a promising approach to supporting tertiary EFL speaking development by integrating creativity, collaboration, and reflective practice. This study contributes a conceptually grounded framework for technology-enhanced language learning and suggests the need for further research on scalable and context-sensitive implementations.